2012
DOI: 10.1155/2012/785262
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisin an Italian Cohort of Type 1 Diabetes Pediatric Patients

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is the etiological agent of Johne's disease in ruminants. Recent studies have linked MAP to type 1 diabetes (T1D) in the Sardinian population. The aim of this study was to investigate the prevalence of MAP infection in a T1D cohort from continental Italy compared with healthy control subjects. 247 T1D subjects and 110 healthy controls were tested for the presence of MAP. MAP DNA was detected using IS900-specific polymerase chain reaction (PCR). The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…Several factors, such as genetic isolation, have likely contributed to the fixing of predisposing alleles. MAP infection is estimated to affect approximately 60% of Sardinian herds [6], and this mycobacterium can be found in pasteurized milk products and may be asymptomatically transmitted to humans [8]. Due to the potential role played by MAP in T1D pathogenesis, it is relevant to better characterize the prevalence of anti-MAP Abs in the Sardinian population.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors, such as genetic isolation, have likely contributed to the fixing of predisposing alleles. MAP infection is estimated to affect approximately 60% of Sardinian herds [6], and this mycobacterium can be found in pasteurized milk products and may be asymptomatically transmitted to humans [8]. Due to the potential role played by MAP in T1D pathogenesis, it is relevant to better characterize the prevalence of anti-MAP Abs in the Sardinian population.…”
Section: Introductionmentioning
confidence: 99%
“…The association of MAP with T1DM has been reported in Sardinia, known to have a high prevalence of type 1 diabetes and a high rate of MAP infection among sheep and cattle [6][7][8]19,27]. However, Rani et al could not find any association despite the high prevalence of MAP and T1DM in India, probably due to the low number of patients investigated [21] or the genetic predisposition of the infected population in developing such an autoimmunity.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have suggested that Mycobacterium avium subsp. paratuberculosis (MAP) is associated with T1DM [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that MAP is the source of mycobacterial HSP65 and thus an environmental trigger for T1D. A large and increasing body of work has subsequently solidified the association of MAP and T1D [83,[108][109][110][111][112][113][114][115][116][117][118][119][120][121]. These studies have also confirmed genetic factors linking risk for MAP and T1D [63].…”
Section: Map Bcg and Autoimmune Diabetesmentioning
confidence: 89%